Memorandum of Understanding between the Institute of Development Studies and BRAC University for the project "Empowerment and participation - linking local realities to global action" (2012) - Institute of Development studies; BRAC Development Institute, BRAC University (Institute of Development Studies and BRAC University, 2013)
1. Introduction. 2. Duration. 3. Terms of reference. 4. Budget. 5. Payment. 6. Legal status. 7. Other contractual conditions. 8. Correspondence. 9. Acceptance.